2001
DOI: 10.1093/humrep/16.4.703
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of XY disomy in spermatozoa of severe oligozoospermic men

Abstract: Frequencies of disomy and diploidy in spermatozoa for chromosomes X, Y and 18 were compared among severe oligozoospermic men (<5x10(6) spermatozoa/ml), oligozoospermic men (5-20x10(6) spermatozoa/ml), and normospermic men using three-colour fluorescence in-situ hybridization (FISH). Semen samples were collected from 10 severe oligozoospermic men aged 26-49 years, 10 oligozoospermic men aged 27-48 years and seven normospermic men aged 25-31 years. Karyotypes in lymphocytes obtained from peripheral blood were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
6
27
4
Order By: Relevance
“…Our results suggested that nondisjunction for chromosomes X and Y can occur at the first and the second meiotic division with the same frequency. Our findings were in discordance with the data of Schmid et al [11] and Ohashi et al [15] who did not show a statistically significant difference in the disomy XX and YY in oligozoospermic men compared to control group. They suggested that chromosomal non disjunction occurs mainly during the first meiotic division [11,15].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results suggested that nondisjunction for chromosomes X and Y can occur at the first and the second meiotic division with the same frequency. Our findings were in discordance with the data of Schmid et al [11] and Ohashi et al [15] who did not show a statistically significant difference in the disomy XX and YY in oligozoospermic men compared to control group. They suggested that chromosomal non disjunction occurs mainly during the first meiotic division [11,15].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings were in discordance with the data of Schmid et al [11] and Ohashi et al [15] who did not show a statistically significant difference in the disomy XX and YY in oligozoospermic men compared to control group. They suggested that chromosomal non disjunction occurs mainly during the first meiotic division [11,15]. In the present study, we did not found an increase in autosomal disomy of chromosome 8.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations